2006
DOI: 10.1016/j.molstruc.2006.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of macrocyclic oligo(phenyldiacetylenes)-II. Synthesis and theoretical study of diacetylenic dehydrobenzoannulene derivatives with weak electron-donor and -acceptor groups

Abstract: Diacetylenic dehydrobenzo [12]annulene and dehydrobenzo [18]annulene derivatives with electron-donor and -acceptor groups were synthesized (including push-pull Eglinton-Galbraith dimer derivative 1c) via an oxidative coupling reaction, and spectroscopically and structurally characterized. The solid-solid phase transition in 1b has been revealed at 45 8C by DSC measurements. Its room temperature crystal structure has been solved by X-ray diffraction measurements. The 1 H and 13 C NMR chemical shifts, UV/vis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The vibrational frequency of a given normal mode, which is essentially composed of chemical groups, can be affected by many intra- and intermolecular interactions, particularly conjugation and hybridization effects. Previous infrared vibrational studies of the carbon–carbon triple bond (CC) , showed that the CC stretching mode in the form of R–CC–R′ is usually IR-inactive if R and R′ are identical and nonaromatic chemical groups. If R and R′ are different hydrocarbon groups, the CC stretching mode becomes weakly IR-active, with a molecular absorption coefficient being even smaller than the C–H group .…”
mentioning
confidence: 99%
“…The vibrational frequency of a given normal mode, which is essentially composed of chemical groups, can be affected by many intra- and intermolecular interactions, particularly conjugation and hybridization effects. Previous infrared vibrational studies of the carbon–carbon triple bond (CC) , showed that the CC stretching mode in the form of R–CC–R′ is usually IR-inactive if R and R′ are identical and nonaromatic chemical groups. If R and R′ are different hydrocarbon groups, the CC stretching mode becomes weakly IR-active, with a molecular absorption coefficient being even smaller than the C–H group .…”
mentioning
confidence: 99%
“…10) are in good agreement with previous DSC measurements. 6,12,13 The exothermic DPB polymerization (120 kJ mol À1 ) is visible in the thermogram at 190 8C, with peak maximum at 240 8C, and analogous behavior is present in the baseline variations of DPB. The decomposition of macrocycles 1 and 2 is an extremely exothermic process.…”
Section: Figmentioning
confidence: 84%
“…Benzoannulenic macrocycles (octadehydrodibenzo [12]annulenes 1, and dodecadehydrotribenzo[18]annulenes 2) were synthesized by Swager's method as previously reported. 5,6 Temperature-dependent behavior of pellets made only of KBr was also measured. They showed linear temperature dependence of absorbance in the 4000-400 cm À1 range at any chosen wavenumber (with average R 2 ¼ 0.994).…”
Section: Methodsmentioning
confidence: 99%
“…500 nm, likely arising from the annulene chromophore red-shifted by the appended pentacenes. [28] While reasonably stable in the solid state, manipulations of solutions of these DHAs were performed with shielding from laboratory light. Even relatively dilute solutions shielded from oxygen showed a half-life of approximately 18 hours (as determined by UV/Vis absorption studies -see Figure S2 in the Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%